Efficient, Selective Removal of Human Pluripotent Stem Cells via Ecto-Alkaline Phosphatase-Mediated Aggregation of Synthetic Peptides. Issue 6 (22nd June 2017) - Kuang, Yi; Miki, Kenji; Parr, Callum J.C.; Hayashi, Karin; Takei, Ikue; Li, Jie; Iwasaki, Mio; Nakagawa, Masato; Yoshida, Yoshinori; Saito, Hirohide
Summary: The incomplete differentiation of human induced pluripotent stem cells (iPSCs) poses a serious safety risk owing to their potential tumorigenicity, hindering their clinical application. Here, we explored the potential of phospho-D-peptides as novel iPSC-eliminating agents. Alkaline phosphatases overexpressed on iPSCs dephosphorylate phospho-D-peptides into hydrophobic peptides that aggregate and induce cell death. We isolated a peptide candidate, D-3, that selectively and rapidly induced toxicity in iPSCs within 1 hr but had little influence on various non-iPSCs, including primary hepatocytes and iPSC-derived cardiomyocytes. Two hours of D-3 treatment efficiently eliminated iPSCs from both single cultures and co-cultures spiked with increasing ratios of iPSCs. In addition, D-3 prevented residual iPSC-induced teratoma formation in a mouse tumorigenicity assay. These results suggest the enormous potential of D-3 as a low-cost and effective anti-iPSC agent for both laboratory use and for the safe clinical application of iPSC-derived cells in regenerative medicine. Graphical Abstract: Highlights: D-3 induces toxicity in iPSCs and ESCs within 1 hr of incubation D-3 has little influence on various non-iPSCs, including hepatocytes and neurons D-3 prevents residual iPSC-induced teratoma formation in an animal model Alkaline phosphatase activity on the cell surface is required for D-3's toxicity Abstract : Yi Kuang et al. discovered a phosphor-peptide D-3 that responds to the activity of alkaline phosphatase on the cell surface to selectively and effectively remove iPSCs and ESCs within 1–2 hr. D-3 is a promising low-cost iPSC-eliminating agent and is simple to use.